The Predictive Ability of the University Grade Point Average in the Specialized Test Score for thAbility of the University Grade Point Average in the Specialized Test Score for the Teacher Position in the Ministry of Education in the Sultanate of Oman (Journal of the College of Education for Women, 2022)
the most important purposes and uses of the test results in the educational sector. This is because the quality of tests is related to their ability to predict the learner's behavior in the future, and the accuracy of the educational and administrative decisions that are taken in light of their results. The study aimed accordingly to reveal the predictive ability of the university Grade Point Average (GPA) in the Score of the specialized test for the position of teacher in the Ministry of Education in the Sultanate of Oman. It further aimed to investigate the differences in the predictive ability according to the specialization and academic year using the descriptive approach. The sample of the study consisted of (349) s/he students enrolled in the educational qualification diploma program at A'Sharqiyah University, who took the specialized test for the position of teacher. The results of the study indicated that the GPA explains (13%) of the variance in the result of the specialized test for the position of teacher. In addition, there are statistically significant differences in the percentage of GPA in the result of the specialized test for the position of teacher to the scientific specialization and in favor of the humanities. Besides, there are no differences in this percentage due to the variable of the academic year. The study has recommended to continue using the SET for the employment purposes and admission to the educational qualification diploma program after making some improvements on it.